Spectral Flux Decomposition in a Wind‐Driven Channel Flow With Near‐Inertial Waves - Michal Shaham; Roy Barkan (Journal of Advances in Modeling Earth Systems)
Abstract In recent years it has become evident that the spatiotemporal distribution of oceanic kinetic energy (KE) is strongly influenced by the interactions between oceanic mesoscale eddies, submesoscale currents, and near‐inertial waves (NIWs). However, the proposed interaction mechanisms remain difficult to evaluate and quantify in complex oceanic numerical simulations. To address these difficulties we introduce an analysis framework that combines spectral KE flux computations across horizontal wavenumbers with temporal filtering and a Helmholtz decomposition, and apply it to idealized, high‐resolution, baroclinic channel solutions consisting of eddies, fronts, and filaments in the O(1) Rossby parameter regime. By comparing solutions with and without NIW forcing we are able to demonstrate that externally forced NIWs lead to a reduction in the inverse KE cascade of the low‐passed eddying flow, and to an enhancement in its forward cascade. These stimulated cascades are associated with the interactions between rotational and divergent eddy motions, characteristic of mesoscale eddies and submesoscale currents, respectively. Additionally, we demonstrate that at larger spatial scales the forward KE cascade of NIWs is accomplished through wave scattering and direct extraction by rotational eddy motions, whereas at smaller spatial scales it is also dominated by wave‐wave interactions. The caveats of our framework, its suitability to investigate eddy‐NIW interactions in realistic oceanic simulations and the disparities between the spectral KE flux and the coarse‐graining methods are also discussed.